MEDIA ONLINE DAN KERJA DIGITAL PUBLIC RELATIONS POLITIK PEMERINTAH PROVINSI DKI JAKARTA - Asep Bidin Rosidin; Abdul Hamid (Universitas Prof. Dr. Moestopo (Beragama), 2020)
Political public relations plays a strategic role in producing and distributing information to the public. Not only that, the ideal must arrive at the level of being able to create solidity and cohesiveness on all fronts. Along with the development of the times, political public relations is required to be adaptive, collaborative and flexible. To fulfill these three aspects, political public realtions must master the use of new media in order to support their work. This research focuses on the study of how political public relations uses new media as a means of supporting the delivery of information. The purpose of this research is to know how the implementation of the use of online media by political public relations within the DKI Jakarta Provincial Government. The research method used by the author is a qualitative method in which data can be obtained through observation and interviews. From observations and interviews, this research results in the fact that political public relations has utilized new media to disseminate information quickly and thoroughly according to the characteristics of new media that can be accessed globally and efficiently.